The Association between Serum Level of Vitamin D and Inflammatory Biomarkers in Hospitalized Adult Patients: A Cross-Sectional Study Based on Real-World Data - Xiaomin Zhang; Zhiqi Chen; Yi Xiang; Yiquan Zhou; Molian Tang; Jun Cai; Xinyi Xu; Hongyuan Cui; Yi Feng; Renying Xu (Mediators of Inflammation)
Objective. The association between vitamin D status and inflammation remains unclear in hospitalized patients. Materials and Methods. We performed the current study based on real-world data from two teaching hospitals. Serum level of vitamin D (assessed by 25-hydroxyvitamin D) was evaluated within 2 days after admission. All the patients were further classified into three groups: deficiency (<12 ng/mL), insufficiency (12–20 ng/mL), and adequate (≥20 ng/mL). White blood cell (WBC) count, serum level of C-reactive protein (CRP), and procalcitonin were also measured and used to evaluate inflammation. Other potential covariates were abstracted from medical records. Charlson comorbidity index (CCI) was calculated to assess the severity of disease. Results. A total number of 35,528 hospitalized adult patients (21,171 men and 14,357 women) were included. The average age and BMI were 57.5 ± 16.2 years and 23.4 ± 3.7 kg/m2, respectively, while medium vitamin D level was 16.1 ng/mL (interquartile range: 11.4 ng/mL, 21.6 ng/mL) and median CCI was one point (interquartile range: 0 point, two points). The prevalence of deficiency and insufficiency was 28.0% and 40.5%. Multivariate linear regression model showed that serum level of vitamin D was significantly associated with WBC and CRP but not associated with procalcitonin. Each standard deviation (≈7.4 ng/mL) increase in vitamin D was associated with a decrease in WBC by 0.13 × 109/mL (95% CI: 0.2 × 109/mL, 0.06 × 109/mL) and 0.62 mg/L (95% CI: 0.88 mg/L, 0.37 mg/L) for CRP. Subgroup analysis and sensitivity analysis (excluding those whose eGFR <60 ml/min/1.73 m2, those whose daily calorie intake <1,000 kcal, and those who were recruited from Xin Hua hospital) generated similar results. Conclusions. The deficiency and insufficiency of vitamin D in the hospitalized adult patients was very common. However, the results should be interpreted with caution for limited representation of the whole inpatients. Low level of vitamin D was associated with inflammatory biomarkers, which provide the evidences to early intervention for lower the risk of infection.